MENGENAL AUTISME PADA ANAK USIA 12 TAHUN SKh 1 KOTA SERANG - Bilqis Raudlatul Anik Nabila; Yahdinil Firda Nadhirah (STKIP Subang, 2024)
This research aims to analyze the condition of children with autism, find out the difficulties in communication and interaction of children with autism and find out the special services provided for children with autism aged 12 years in SKh 1 Serang city. This research uses a qualitative approach with a case study method. The subject of this research was one autistic child and several key informants such as teachers and parents. Data collection was carried out through observation, interviews and documentation. The observation results show several challenges, difficulties, and obstacles experienced by autistic children